1998
DOI: 10.1093/jhered/89.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variability in Grauer's gorillas of Kahuzi-Biega National Park

Abstract: Eastern lowland gorillas (Gorilla gorilla graueri) are the least studied of the three gorilla subspecies; particularly at the molecular level. We sequenced an internal region of the mitochondrial DNA cytochrome oxidase subunit II (COII) region and a hypervariable portion of the mitochondrial DNA control region (D-loop) from wild gorillas in both the montane and lowland habitats of Kahuzl-Blega National Park, Democratic Republic of Congo. All individuals (n = 38) were identical at the COII region; this sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
3
26
0
1
Order By: Relevance
“…The differing result may arise from the small population size and limited migratory range of the Oriental white stork, and more precise analysis is required of the wild population in China and Russia. The nucleotide variations in the D-loop region have been studied to reveal the genetic variation in, and population structure of, the chum salmon (Park et al 1993), the dunlin (Wenink and Baker 1996), the green turtle (Encalada et al 1996), the kokanee (Taylor et al 1997), the Japanese sika deer (Nagata et al 1998), the Asian water buffalo (Lau et al 1998), the Japanese golden eagle ) and the eastern lowland gorilla (Saltonstall et al 1998). Only four nucleotide differences were found among 16 chum salmon individuals (Park et al 1993), while 33 haplotypes were identified among 80 water buffalo individuals (Lau et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The differing result may arise from the small population size and limited migratory range of the Oriental white stork, and more precise analysis is required of the wild population in China and Russia. The nucleotide variations in the D-loop region have been studied to reveal the genetic variation in, and population structure of, the chum salmon (Park et al 1993), the dunlin (Wenink and Baker 1996), the green turtle (Encalada et al 1996), the kokanee (Taylor et al 1997), the Japanese sika deer (Nagata et al 1998), the Asian water buffalo (Lau et al 1998), the Japanese golden eagle ) and the eastern lowland gorilla (Saltonstall et al 1998). Only four nucleotide differences were found among 16 chum salmon individuals (Park et al 1993), while 33 haplotypes were identified among 80 water buffalo individuals (Lau et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Further analyses of the cytochrome oxidase II mitochondrial gene by Ruvolo et al [1994] support a deep split between eastern and western clades. More recent sequence data from 64 individuals of the eastern lowland gorilla Gorilla gorilla graueri [Saltonstall et al, 1998] confirm the diagnostic power of these sites. Additional supporting data may lead to a revision of gorilla taxonomy with the eastern and western clades receiving species status rather than sub-specific designations.…”
Section: Introductionmentioning
confidence: 86%
“…Total genomic DNA was extracted from the sample following a standard phenol/chloroform procedure [Caccone et al, 1987]. A fragment of the cytochrome oxidase II mitochondrial gene was polymerase chain reaction (PCR) amplified using gorilla-specific primers [Amato and Gatesy, 1994;Ruvolo et al, 1994;Saltonstall et al, 1998]. Amplifications were performed in a Perkin-Elmer 9600 thermal cycler (Perkin-Elmer, Wellesley, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years mtDNA sequence data have been used to examine the genetic diversity of apes following the great wave of human mtDNA diversity studies (e.g., Gagneux et al 1999;Garner and Ryder 1996;Goldberg and Ruvolo 1997;Morin et al 1994;Muir et al 2000;Ruvolo et al 1994;Saltonstall et al 1998;Warren et al 2001;Wise et al 1997;Zhi et al 1996). However, even those already published mtDNA sequence data seem to be insufficient for estimating the genetic diversity of apes, in particular, orangutans and gibbons.…”
mentioning
confidence: 99%